Influence of Bias Voltage on the Microstructure, Mechanical and Corrosion Properties of Ti/CrN/TiN Multilayered Films Deposited by Cathodic Arc Evaporation - Vu Van Huy; Nikolay B. Rodionov; Valery А. Karpov; Ngo Thanh Binh; Nguyen Dang Khoa; Vu Thi Lan Vi (Tribology in Industry)
Ti/CrN/TiN multilayer coatings were deposited via cathodic arc deposition at substrate bias voltages ranging from 20 V to 60 V. The study investigated the effects of bias voltage on the coatings microstructure, mechanical properties, and corrosion properties using laser and scanning electron microscopy, X-ray diffraction, nanohardness testing, and electrochemical testing equipment. The results indicate that bias voltage significantly influences the morphologies of Ti/CrN/TiN coatings. As the bias voltage increased from 20 V to 60 V, the concentration of macroscopic defects decreased markedly, and the average surface roughness (Ra) reduced from 0.227 µm to 0.179 µm. Nanoindentation revealed that coatings deposited at a bias voltage of 60 V exhibited a notable enhancement in hardness and elastic modulus. Corrosion testing in a 3.5 wt.% NaCl solution showed that coatings deposited at bias voltages of 20 V and 40 V had better corrosion resistance compared to those deposited at 60 V, likely due to the denser microstructure acting as a barrier to the diffusion of corrosive substances.